Instagram Usage by "Barstrad" Community in Bandung City – West Java - Gumgum Gumilar; Ika Merdekawati Kusmayadi (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2017)
This study aims to collect qualitative data on Instagram Usage by Community of Bandung Street Workout Addict (Barstrad) in Bandung City, West Java. This study is applied descriptive method and collecting the data through depth interview and observation. The informant of this research is the founder Bastard community. The result shows that Instagram has significant role in developing of Barstard community, especially in terms of spreading out of street workout in Bandung City. Instagram is managed with a certain concept by informing the main activities, workout menus, schedules, and others as well. Instagram gives a huge impact on the increasing number of members who join in. Most of the member community are from Instagram followers that also make this community more well recognized and attracts sponsor in order to be a kind of sustainable community.Â